PENGARUH KOMPENSASI, KEPEMIMPINAN, DAN KOMITMEN ORGANISASI TERHADAP KEPUASAN KERJA PEGAWAI (Survei pada Pegawai Dinas Perhubungan Kabupaten Sragen) - Syamsulhaq, Syamsulhaq; Suddin, Alwi; Widajanti, Erni (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2019)
Job satisfaction is essentially an individual thing, each person will have a level of satisfaction that is not the same as the value system that applies to him. The more aspects of the job that suit the person's desires, the higher the satisfaction he feels. Vice versa, if the fewer aspects of the job in accordance with the wishes of people, the lower the level of satisfaction. This study aims to determine the effect of 1) compensation on job satisfaction, 2) leadership on satisfaction, 3) and organizational commitment to job satisfaction. Respondents in this study were all employees of the Transportation Agency of Sragen Regency with 66 employees using saturated sampling techniques. Data collected through a questionnaire was then tested with validity and reliability tests. Hypothesis analysis uses multiple linear regression, t test, F test and the coefficient of determination (R2). The analysis shows that (1) compensation has a positive and significant effect on job satisfaction; (2) leadership has a positive and significant effect on job satisfaction; and (3) organizational commitment has a positive and significant effect on job satisfaction. The higher compensation, leadership and organizational commitment, the higher the job satisfaction, and vice versa the lower the compensation, leadership and organizational commitment, the lower the job satisfaction.